Rural water supply and sanitation = (The World Bank in Vietnam (WB), 2004)
This project paper provides an additional credit to the Socialist Republic of Vietnam for first phase of the Red River Delta Rural Water Supply and Sanitation Project. The additional credit will help finance the costs associated with completion of the original project activities within the same project areas that could not be finished as a result of unanticipated cost over-runs. The cost over-runs are due to high inflation and design changes necessary due to increased demand for connections and capacity in the original project